2014
DOI: 10.1097/mao.0000000000000506
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Paraclinical Tests in the Diagnosis of Cervicogenic Dizziness

Abstract: This study showed differences in sensorimotor disturbances between the two groups, particularly in the control of head and eye movements and cervical proprioception. Patients with cervicogenic dizziness were more likely to (1) have a sensation of drunkenness and lightheadedness, (2) have pain induced during the physical examination of the upper cervical vertebrae, (3) have an elevated joint position error of 4.5 degrees during the cervical relocation test, and (4) exhibit more than 2 degrees per second nystagm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 26 publications
2
90
0
8
Order By: Relevance
“…67 Conversely, reproduction of symptoms during en bloc tests (ie, simultaneous trunk and head rotation) should indicate a noncervical cause. 49 Associated findings of musculoskeletal impairment in the cervical spine, especially the upper cervical spine, have been shown to be important in those with cervicogenic dizziness 67,86 ; however, this is usually present in those with traumatic neck pain and thus not specifically helpful for differential diagnosis in this group. A potential schema for differential diagnosis, possible subjective and objective test findings, and subsequent management that may be required are presented in the [ clinical commentary ]…”
Section: Differential Diagnosismentioning
confidence: 99%
See 3 more Smart Citations
“…67 Conversely, reproduction of symptoms during en bloc tests (ie, simultaneous trunk and head rotation) should indicate a noncervical cause. 49 Associated findings of musculoskeletal impairment in the cervical spine, especially the upper cervical spine, have been shown to be important in those with cervicogenic dizziness 67,86 ; however, this is usually present in those with traumatic neck pain and thus not specifically helpful for differential diagnosis in this group. A potential schema for differential diagnosis, possible subjective and objective test findings, and subsequent management that may be required are presented in the [ clinical commentary ]…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Recently, it has been suggested that nystagmus of greater than 2°/s during sustained neck torsion positions may be an alternative and more sensitive method than SPNT to demonstrate these abnormalities. 67 However, this was done in individuals with cervicogenic diz-ziness and not specifically in those with traumatic neck pain.…”
Section: Smooth-pursuit Neck Torsionmentioning
confidence: 99%
See 2 more Smart Citations
“…Esta propiocepción, que parte fundamentalmente de las carillas articulares de C1-C3 [11][12], participa también en el control postural (desequilibrio de origen cervical) y se supone responsable del reflejo cérvico-ocular (RCO), cuya presencia complementa al reflejo vestíbulo-ocular (RVO) en frecuencias lentas de movimiento [13]. La función de estos mecanorreceptores y nociceptores puede alterarse por traumatismo, fatiga muscular, cambios degenerativos o por efecto directo del dolor [14]. Pero falta de discernir, si las lesiones del cuello pueden llegar a influir, de manera significativa, en los sistemas oculomotor y vestibular humano [2].…”
Section: Cervicogénicounclassified